Phase Equilibrium Diagram for Electric Arc Furnace Slag Optimization in High Alloyed Chromium Stainless Steelmaking - Marcus Kirschen; In-Ho Jung; Gernot Hackl (Metals, 2020)
The electric arc furnace (EAF) process for steelmaking of Cr and Ni high alloyed stainless steel grades differs significantly from the steelmaking process of carbon steel due to the special raw materials and generally lower oxygen consumption. The special slag chemistry in the EAF process affects slag foaming and refractory wear characteristics due to an increased content of CrOx. A special slag diagram is presented in order to improve monitoring and control of slag compositions for Cr alloyed heats, with special focus on saturation to MgO periclase and dicalcium silicate C2S in order to minimize MgO losses from the refractory lining and to improve slag refining capability by avoidance of stable C2S. With the same diagram different EAF process strategies can be efficiently monitored, either at elevated CaO and basicity with lower spinel concentration and more liquid process slags near C2S saturation or at lower CaO content and basicity with increased spinel concentration and stiffer slags at MgO saturation but certainly no C2S stability. Examples for three industrial EAFs are given.